2014
DOI: 10.2478/s13536-014-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of substrate temperature on the growth mechanism and physical properties of spray deposited lead oxide thin films

Abstract: Thin films of lead oxide were synthesized by cost effective spray pyrolysis technique at different substrate temperatures on glass substrates. Effect of substrate temperature on the growth mechanism and physical properties of the films was investigated. All the films were polycrystalline in nature with tetragonal structure corresponding to α-PbO. The films coated at 225°C and 275°C were (1 0 1) oriented, while the films deposited at 325°C and 375°C were (0 0 2) oriented. Above 375°C, the pure tetragonal nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 32 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…At the occurrence of this fact, the films were repeatedly deposited at this temperature a couple of times with variation of thickness still in the reported range. A very similar report has been given by [2], citing [14] wherein the various authors concluded that at higher temperatures there is a reduction in the transfer of precursor to the substrate. This, [2] and [14] attributed to gas convection emanating from the chamber, hence pushing away the droplets from the substrate surface leading to the development of crystallites within the vapour.…”
Section: Fig 2 Transmission Spectra For Mgse:eu Films At Varying Susupporting
confidence: 63%
“…At the occurrence of this fact, the films were repeatedly deposited at this temperature a couple of times with variation of thickness still in the reported range. A very similar report has been given by [2], citing [14] wherein the various authors concluded that at higher temperatures there is a reduction in the transfer of precursor to the substrate. This, [2] and [14] attributed to gas convection emanating from the chamber, hence pushing away the droplets from the substrate surface leading to the development of crystallites within the vapour.…”
Section: Fig 2 Transmission Spectra For Mgse:eu Films At Varying Susupporting
confidence: 63%
“…Fig. 2 shows the variation of the preferential orientation factor f(h k l) of the (1 1 1) plane calculated by the way adopted by Suganya et al [15] as a function of aging period of the starting solution. It is observed that f(1 1 1) increases with an increase in aging period of the starting solution, attaining a maximum value for the CdO film prepared from 3-days aged solution and for further increase in aging period it slightly decreases.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is observed that preferred orientation along (0 2 10) direction changes to (5 0 8) direction with Pb doping. The minimization in surface energy and internal stress might be dominating the occurrence of preferential orientation [47][48][49][50][51][52]. These observations reveal that growth direction of examined nanocrystalline composition changes with Pb amount.…”
Section: Methodsmentioning
confidence: 80%